Complications and risk management in the use of the reaming-irrigator-aspirator (RIA) system: RIA is a safe and reliable method in harvesting autologous bone graft - Haubruck, Patrick; Ober, Julian; Heller, Raban; Miska, Matthias; Schmidmaier, Gerhard; Tanner, Michael Christopher (PLOS ONE, 2018)
Background Autologous bone grafting (ABG) remains the gold standard for augmentation of bone defects. The RIA system has become more prevalent, but evidence regarding risk management and complications remain scarce. This study presents the risk management and complications associated with RIA in the largest single-center case series to date. Methods All records, operative notes, lab data and radiographs of patients receiving a RIA procedure at Heidelberg´s University Hospital between 01/01/2010 and 31/12/2016 were reviewed. Multivariate logistic regression models adjusting for clinically relevant covariates were used to examine the respective relevance regarding the presence and absence of prolonged postoperative pain (PPP). Results A total of 341 RIA procedures on 306 patients were performed at our level-1 trauma center. The femur was the main donor site (98.53%; N = 336) whereas only in 1.47% (N = 5) the tibia was utilized. A total of 11 patients showed a relevant loss of hemoglobin requiring blood transfusion. A total of 22 patients suffered from PPP directly associated with the RIA procedure resulting in prevalence of 6.45%. The 6 major complications in our study were of diverse origin and all intraoperative complications took place in the early phase of the RIA procedure in our center (2010-2013). Our data revealed influence of sex (p = 0.0459) and age (p = 0.0596) on the criterion PPP. The favored model including sex and age resulted in an AUC of 66.2% (CI: 55.5%-76.9%). Conclusion Perioperative blood loss remains a prevalent complication during RIA reaming. In addition, PPP occurs with a prevalence of 6.45%. This study showed a complication rate of 1.76%, emphasizing RIA´s overall safety and furthermore highlighting the need for vigilance in its application and prior extensive hands-on training of surgeons. Level of Evidence: II.